RECURRENCE RATE AFTER MESH REPAIR OF INGUINAL HERNIA: A CLINICAL STUDY - Dr. Mohammed Haroon Malik; Dr. Mumtaz Ali Khan; Dr Ibrar Ahmad; Dr. Israr ul Haq; Dr. Valeeja Zafar; Dr. Mashaim Fatima (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Inguinal hernia repair is among the most common general surgical procedures. Mesh repair, especially via the Lichtenstein tension-free technique, has become the gold standard due to reduced recurrence rates compared to tissue repair. This study aimed to evaluate the postoperative outcomes and recurrence rate after mesh repair in a tertiary care setup. Methodology: A prospective observational study was conducted in the Department of Surgery, Abbottabad International Medical College, between January and December 2024. A total of 100 patients with primary inguinal hernia underwent open mesh repair using the Lichtenstein technique. Patients with recurrent or complicated hernias were excluded. Postoperative complications and recurrence rates were documented. Follow-up was carried out at 1 month, 6 months, and 12 months. Results: Of the 100 patients, 92 were male and 8 were female, with a mean age of 44 ± 12 years. Right-sided hernia was more common (58%), followed by left-sided (34%) and bilateral (8%). Early postoperative complications included seroma formation in 5% (n=5), wound infection in 3% (n=3), and chronic groin pain in 6% (n=6). The recurrence rate at 12 months was 2% (n=2). Conclusion: Mesh repair of inguinal hernia using the Lichtenstein technique provides favorable postoperative outcomes with minimal complications and a low recurrence rate. It remains a safe and effective option in our surgical practice.